Maternal Toxoplasma gondii infection affects proliferation, differentiation and cell cycle regulation of retinal neural progenitor cells in mouse embryo - Campos, Viviane Souza de; Magalhães, Camila Feitosa; da Rosa, Barbara Gomes; dos Santos, Carolina Moreira; Fragel-Madeira, Lucianne; Figueiredo, Danniel Pereira; Calaza, Karin C.; Adesse, Daniel (Frontiers in Cellular Neuroscience, 2023)
Toxoplasmosis affects one third of the world population and has the protozoan Toxoplasma gondii as etiological agent. Congenital toxoplasmosis (CT) can cause severe damage to the fetus, including miscarriages, intracranial calcification, hydrocephalus and retinochoroiditis. Severity of CT depends on the gestational period in which infection occurs, and alterations at the cellular level during retinal development have been reported. In this study, we proposed a mouse CT model to investigate the impact of infection on retinal development. Pregnant females of pigmented C57BL/6 strain mice were infected intragastrically with two T. gondii cysts (ME49 strain) at embryonic day 10 (E10), and the offspring were analyzed at E18. Infected embryos had significantly smaller body sizes and weights than the PBS-treated controls, indicating that embryonic development was affected. In the retina, a significant increase in the number of Ki67-positive cells (marker of proliferating cells) was found in the apical region of the NBL of infected mice compared to the control. Supporting this, cell cycle proteins cyclin D3, Cdk6 and pChK2 were significantly altered in infected retinas. Interestingly, the immunohistochemical analysis showed a significant increase in the population of β-III-tubulin-positive cells, one of the earliest markers of neuronal differentiation. Our data suggests that CT affects cell cycle progression in retinal progenitor cells, possibly inducing the arrest of these cells at G2/M phase. Such alterations could influence the differentiation, anticipating/increasing neuronal maturation, and therefore leading to abnormal retinal formation. Our model mimics important events observed in ocular CT.